2006
DOI: 10.2131/jts.31.123
|View full text |Cite
|
Sign up to set email alerts
|

Acute Toxicity of Pierisin-1, a Cytotoxic Protein From Pieris Rapae, in Mouse and Rat

Abstract: -To investigate the toxicity of pierisin-1, a cytotoxic protein present in the cabbage butterfly, Pieris rapae, pierisin-1 was administered via intraperitoneally in mice and rats and the effects examined. Common findings in these experiments were hypoactivity with a gradual decrease in body weight due to decreased food intake, relative polycythemia with low serum albumin concentration and atrophy of the thymus, spleen, seminal vesicles and adipose tissue. Characteristic findings were diarrhea, fusion and atrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Especially, to evaluate systemic toxicity of anti-Flt1-EBP12, the acute toxicity test was performed to investigate its biosafety. As reported, the drug is intra-peritoneally administered once, and mortality, body weight, and behavioral changes of the mice are observed for 7 days to test any acute toxicity. A single intraperitoneal injection of anti-Flt1-EBP12 had no effect on mice survival.…”
Section: Resultsmentioning
confidence: 99%
“…Especially, to evaluate systemic toxicity of anti-Flt1-EBP12, the acute toxicity test was performed to investigate its biosafety. As reported, the drug is intra-peritoneally administered once, and mortality, body weight, and behavioral changes of the mice are observed for 7 days to test any acute toxicity. A single intraperitoneal injection of anti-Flt1-EBP12 had no effect on mice survival.…”
Section: Resultsmentioning
confidence: 99%
“…Oxidative stress is considered to serve an important role in the development of CCl 4 -induced acute liver injury (33,34). When CCl 4 enters the liver and is activated by cytochrome P450 metabolism, it generates various free radicals and reactive oxygen species for oxidative stress and causes membrane lipid peroxidation (14,15). The activity of SOD, an effective metalloenzyme which catalyzes the dismutation of superoxide anions into H 2 O 2 and O 2 (35)(36)(37), was markedly increased compared with the injury group.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that following activation by cytochrome P450 metabolism in the liver, CCl 4 generates numerous free radicals and reactive oxygen species which cause oxidative stress. These species cause membrane lipid peroxidation and bind protein macromolecules through covalent linkage, ultimately leading to interference with protein function, the destruction of cell membrane structure, increased permeability of the cell membrane, leakage of liver enzymes and liver cell death (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…strains and Streptosporangium roseum, and an imperfect ORF remains in Streptomyces avermitilis (Szirák et al 2012;Nakano et al 2013). Contrary to pierisins, MTX, and Plx1, which shows toxicity (Shiga et al 2006;Thanabalu et al 1991;Schirmer et al 2002;Fünfhaus et al 2013), physiological roles for SCO5461 might not be toxin due to the lack of receptor-binding domains. Szirák et al (2012) have reported the possible ADP-ribosylation of a 65-kDa endogenous protein by SCO5461, and that a disruption of the SCO5461 gene affects sporulation and antibiotic production depending on the culture conditions.…”
Section: Homologues Of the Pierisins And Carp-1mentioning
confidence: 99%